Seasonal variability of eddy kinetic energy in the East Australian current region - Liu, Jia; Zheng, Shaojun; Feng, Ming; Xie, Lingling; Feng, Baoxin; Liang, Peng; Wang, Lei; Yang, Lina; Yan, Li (Frontiers in Marine Science, 2022)
The East Australian Current (EAC) is an important western boundary current of the South Pacific subtropical Circulation with high mesoscale eddy kinetic energy (EKE). Based on satellite altimeter observations and outputs from the eddy-resolving ocean general circulation model (OGCM) for the Earth Simulator (OFES), the seasonal variability of EKE and its associated dynamic mechanism in the EAC region are studied. High EKE is mainly concentrated in the shear-region between the poleward EAC southern extension and the equatorward EAC recirculation along Australia's east coast, which is confined within the upper ocean (0-300 m). EKE in this area exhibits obvious seasonal variation, strong in austral summer with maximum (465±89 cm² s-²) in February and weak in winter with minimum (334±48 cm² s-²) in August. Energetics analysis from OFES suggests that the seasonal variability of EKE is modulated by the mixed instabilities composed of barotropic and baroclinic instabilities confined within the upper ocean, and barotropic instability (baroclinic instability) is the main energy source of EKE in austral summer (winter). The barotropic process is mainly controlled by the zonal shear of meridional velocities of the EAC southern extension and the EAC recirculation. The poleward EAC southern extension and the equatorward EAC recirculation are synchronously strengthened (weakened) due to the local positive (negative) sea level anomalies (SLA) under geostrophic equilibrium, and the barotropic instability dominated by zonal shear is enhanced (slackened), which results in a high (low) level of EKE in the EAC region.